2019
DOI: 10.3390/ani9070458
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Tail Biting Events in Finisher Pigs from Automatically Recorded Sensor Data

Abstract: Tail biting in pigs is an animal welfare problem, and tail biting should be prevented from developing into tail damage. One strategy could be to predict events of tail biting so that the farmer can make timely interventions in specific pens. In the current investigation, sensor data on water usage (water flow and activation frequency) and pen temperature (above solid and slatted floor) were included in the development of a prediction algorithm for tail biting. Steps in the development included modelling of dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 23 publications
5
25
0
Order By: Relevance
“…Most publications used camera technology (49%), followed by microphones (18%) and animal attached sensors (15%) including accelerometers and RFID tags. Sensor technology used to measure environmental biomarkers include thermometers (n = 8, [12][13][14][15][16][17][18][19]), an EMK ('Environmental Monitoring Kit', n = 1, [20]), an anemometer (n = 1, [18]), an air-speed transmitter (n = 1, [15]), and a weather station (n = 1, [21]) used to measure temperature, relative humidity, air velocity, ventilation rate, CO 2 , and ammonia.…”
Section: Sensor Technologymentioning
confidence: 99%
“…Most publications used camera technology (49%), followed by microphones (18%) and animal attached sensors (15%) including accelerometers and RFID tags. Sensor technology used to measure environmental biomarkers include thermometers (n = 8, [12][13][14][15][16][17][18][19]), an EMK ('Environmental Monitoring Kit', n = 1, [20]), an anemometer (n = 1, [18]), an air-speed transmitter (n = 1, [15]), and a weather station (n = 1, [21]) used to measure temperature, relative humidity, air velocity, ventilation rate, CO 2 , and ammonia.…”
Section: Sensor Technologymentioning
confidence: 99%
“…Water flow meters have been used in a study for predicting tail biting outbreaks by combining the frequency of use of water points and ambient temperature (108). Image analysis was also used for recognizing movement and location associated to walking, running, exploring, playing, nursing, feeding, urinating and mounting.…”
Section: Other Behaviormentioning
confidence: 99%
“…The study by was the first one to consider the dynamic modelling of water drinking patterns and demonstrated its power in detecting disease outbreaks . One way to measure water intake is to utilise water meters, and multiple studies have found predictive information in this measure when considering unwanted events within the pig production including tail biting, pen fouling and diarrhoea (Jensen et al, 2017;Dominiak et al, 2019;Larsen et al, 2019). Other approaches focus less on the precise water consumption of the animals and instead focus more on the frequency and duration of the visits to the drinker.…”
Section: Applications Of Monitoring Technologies In the Production Prmentioning
confidence: 99%